EVALUATION OF THE OBJECTIVES POLARIZATION DISCRIMINATION AGAINST PASSIVE HINDRANCES WITH THE DEVICE, BASED ON CONSIDERATION OF THE SPATIAL VARIATION OF THE FARADAY ROTATION ANGLE IN THE PLANE OF POLARIZATION IS IONIZED MEDIUM SIGNAL - Volodymyr I. Mirnenko; Evgen A.Yufa A. Yufa; Maxim N. Zhuravskij (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The paper analyzes the studies of incoherently scattered ionospheric radio signals of long duration. The depolarization of the incoherently scattered signal was experimentally of incoherently scattered detected, which is due to the spatial variation of the Faraday rotation angle in the ionosphere of the signal polarization plane. It is proposed to use this effect for polarization selection of simple geometric shapes against the background of interference reflections from inhomogeneities in the electron concentration of the ionized medium. Also, a device was developed that implements the proposed method of polarization target selection. The scheme of the proposed polarization selection device contains two circular polarization antennas of the opposite direction of rotation, two optimal filters, two quadrature channels of synchronous detectors, four multipliers, two adders, two narrowband filters and a functional converter. It is assumed that the transmitting antenna is linearly polarized. In order to determine the operability of the device under various conditions and to evaluate its efficiency, the signal-to-noise ratio at the output of the device is calculated in the case where the backscattering matrix of the target and the matrix of the interference element (for example, dipole, angle reflector, etc.) are not diagonal, m .e. when a cross-polarization component appears when the signal from the target or from the interference element is reflected.